A BESSEL DELTA METHOD AND EXPONENTIAL SUMS FOR GL(2). (8th July 2020) - Aggarwal, Keshav; Holowinsky, Roman; Lin, Yongxiao; Qi, Zhi
Abstract: In this paper, we introduce a simple Bessel $δ $ -method to the theory of exponential sums for $GL_2$ . Some results of Jutila on exponential sums are generalized in a less technical manner to holomorphic newforms of arbitrary level and nebentypus. In particular, this gives a short proof for the Weyl-type subconvex bound in the $t$ -aspect for the associated $L$ -functions.